Implications of Veterinary Medicine in the comprehension and stewardship of antimicrobial resistance phenomenon. From the origin till nowadays. - Cristina Vercelli; Graziana Gambino; Michela Amadori; Giovanni Re (Veterinary and Animal Science, 2022)
Antimicrobial resistance (AMR) is defined by the entire scientific community as the major threat for human health and it is responsible for an increase in morbidity and mortality rates. The reasons behind this phenomenon are complex and the solution is achievable only considering the One Health approach, that encompasses the integration and implementation of human health, veterinary medicine and environmental status. Authors aimed to write this review to summarize to readers the three milestones of One-Health, underlying the most important topics in which veterinary medicine is mostly involved. Therefore, a short introduction about the history of AMR in veterinary medicine is provided, then more detailed aspects about the impact of AMR related to pets, food producing animals, wild animals and environment are discussed. Finally, some critical aspects about current and future issues are considered.